OSTEOPOROSIS IN ELDERLY PATIENTS WITH CHRONIC KIDNEY DISEASE: PREVALENCE AND ASSOCIATED FACTORS - Minh Quân, Nguyễn; Tam, Võ (Journal of Health and Aging, 2025)
Osteoporosis is a common complication in elderly patients with chronic kidney disease (CKD), particularly at fracture-prone sites such as the femoral neck. However, osteoporosis screening in this population remains insufficient in routine clinical practice, especially in Vietnam. This study aimed to determine the prevalence of osteoporosis and its associated factors in patients aged ≥70 years with CKD. A cross-sectional study was conducted on 76 patients aged ≥70 years with stage 3–5 CKD (including 47 predialysis and 29 maintenance hemodialysis patients) at Thong Nhat Hospital from September 2022 to June 2024. Clinical and laboratory data were collected, and bone mineral density (BMD) was measured using DXA at three sites: lumbar spine (LS), total hip (TH), and femoral neck (FN). Logistic regression was used to identify predictors of osteoporosis, with model accuracy evaluated by AUC. The overall prevalence of osteoporosis was 43.4%, highest at the femoral neck (40.8%). Mean BMD at the femoral neck (0.559 ± 0.147 g/cm²) was significantly lower than at the total hip (0.713 ± 0.168) and lumbar spine (0.901 ± 0.209; p < 0.001). Independent protective factors included male sex (OR = 0.082; p < 0.001) and higher BMI (OR = 0.670; p = 0.004). Maintenance hemodialysis was identified as an independent risk factor (OR = 4.368; p = 0.027). The predictive model incorporating these three variables achieved good accuracy (AUC = 0.89). Patients aged ≥70 years with CKD—particularly women, those with low BMI, and those on maintenance hemodialysis—are at high risk of osteoporosis, especially at the femoral neck. Routine BMD screening should be implemented for early detection and timely intervention.
Keywords: osteoporosis; chronic kidney disease; elderly